Effects of Soil Ameliorants on Growth And Yield of Elephant Grass (Pennisetum Pupureum) in Post-Tin Mining Land - Tri Lestari; Nyayu Siti Khodijah; Nanda Sukowati Pratiwi; Deni Pratama (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2025)
Post-tin mining land is dominated by sand fractions and low in organic C content and essential macronutrients. A high yield of elephant grass can be produced on land containing sufficient and constantly available nutrients. This research aimed to determine the effects of mycorrhizae and NPK fertilizer ameliorants on the growth and yield of elephant grass plants in post-tin mining land. This research was arranged in a randomized complete block design with a combination of mycorrhizae and NPK fertilizer doses. Treatments consisted of control (without mycorrhizae and NPK), NPK 100%, mycorrhizae + NPK 25%, mycorrhizae + NPK 50%, and mycorrhizae + NPK 100%. The recommended dose of NPK 100% was 300 kg/ha. The research results demonstrated the significant effects of the combination of mycorrhizae and NPK fertilizer doses on the plant height, number of clumps, and crop production per plot. Applying NPK fertilizer 100% to elephant grass plants resulted in the highest ratoon yields in post-tin mining land.